2007
DOI: 10.1287/moor.1060.0236
|View full text |Cite
|
Sign up to set email alerts
|

A Multiperiod Newsvendor Problem with Partially Observed Demand

Abstract: We consider a newsvendor problem with partially observed Markovian demand. Demand is observed if it is less than the inventory. Otherwise, only the event that it is larger than or equal to the inventory is observed. These observations are used to update the demand distribution from one period to the next. The state of the resulting dynamic programming equation is the current demand distribution, which is generally infinite dimensional. We use unnormalized probabilities to convert the nonlinear state transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 10 publications
0
55
0
Order By: Relevance
“…Ding et al (2002) and Lu et al (2005Lu et al ( , 2006 extend this "stock more" result to perishable inventory systems with a general continuous demand distribution. Bensoussan et al (2005) study a similar problem with Markovian demand.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al (2002) and Lu et al (2005Lu et al ( , 2006 extend this "stock more" result to perishable inventory systems with a general continuous demand distribution. Bensoussan et al (2005) study a similar problem with Markovian demand.…”
Section: Introductionmentioning
confidence: 99%
“…Bensoussan et al [17] proposes an estimation method based on observed demands using dynamic programming and probability theory. Levi et al [18] use the Monte Carlo simulations to estimate the demand distribution for both single newsvendor and multi-period newsvendor problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The (discrete) multiperiod newsvendor problem has been studied in detail by many authors, Matsuyama (2004), Berling (2006), Bensoussan et. al (2007Bensoussan et.…”
Section: Introductionmentioning
confidence: 99%